(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Groundwater represent an excellent source of water due to its renewable nature, its availability throughout the year and relatively high quality than surface water. However it is more difficult to remediate a contaminated groundwater source. So due to the fact that about 90% of the citizens make use of groundwater for drinking and other domestic purposes, It is therefore, necessary for groundwater to be safe from any form of contamination. The 2D-Electrical Resistivity Tomography (2D-ERT) were carried out with the aim to investigate groundwater contamination in Akwanga town, Nasarawa State Nigeria. Nine (9) profiles of 2D-ERT was conducted along two dumpsites and one abattoir within the study area employing the dipole-dipole array with inter electrode spacing of 2.5 m which covers a total lateral distance of 100 m thereby allowing for about 15 m depth of investigation below the subsurface, Abem SAS 4000 terameter was used for the data acquisitions while the data interpretation was carried out using Res2Dinvers software for the 2D-ERT respectively. The 2D-ERT results revealed the presence of contaminated plume (leachate) within the investigated area with true resistivity model revealing anomaly of very low resistivity of <20 m from top soil down to a maximum depth of about 15 m, this low resistivity value is associated with leachate due to the dumpsite and abattoir respectively, the 2D structures has shown various conductive path ways via fractures and openings, thus contaminating the groundwater. I recommend that further geochemical analysis of the water should be done to ascertain the...